CONSTRUCTIVE FACTORS DEFINING RELIABILITY OF THE ENERGY SUPPLY SYSTEM - Nakashidze, I.; Tonkoshkur, A.; Uglanov, G.; Parfilko, A. (Institute of Renewable Energy National Academy of Sciences of Ukraine, 2018)
One possible way to use the energy of the sun is to convert it into thermal energy with the help of solar collector systems. Efficiency and reliability of operation of power supply systems with solar collectors depends on the choice of the structural elements of the converter. The operational properties of the power supply system are affected by a number of conditions, among them the physicochemical properties of structural components. The purpose of this paper is to determine the selection criteria for the coolant for various solar collector designs in the power supply system. Over the years of solar energy development, many reservoir designs have appeared, but there are three types in the basics: open, flat, vacuum. When designing power supply systems, one of the determining factors is the reliability of solar radiation conversion elements. They must efficiently convert the energy of solar radiation for a long time. At the same time, their performance indicators should be stable throughout the life cycle. Therefore, for the solar collector system of any of the above types of construction, it is important to choose the coolant. To increase the reliability of the energy supply system with the solar collector, the coolant must be pre-filtered. One of the most common coolants in solar collector systems is water. To increase the reliability of operation of systems operating in the cold season, it is proposed to use a solution based on propylene glycol as a heat carrier. The solar collector system can be made of various materials. At the stage of designing a reliable system of solar collectors, it is necessary to take into account the advantages and disadvantages, as well as the chemical and physical properties of the coolant.